Electrolyte layer preparation method, electrolyte, battery cell and solid-state battery

CN123018107APending Publication Date: 2026-10-30SHENZHEN SHANGLIDE NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611316153.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,固态电池中电解质层与正负极间会产生界面接触问题,降低固态电池的界面本征稳定性

Benefits of technology

[0014]本申请实施例提供的电解质层制备方法、电解质、电芯及固态电池,其中,该方法包括:将硫化物膜和卤化物膜层叠,形成多膜层结构;对多膜层结构进行热辊压,得到电解质层;热辊压的温度大于硫化物膜和卤化物膜中粘结剂的二次玻璃化转变温度,且小于硫化物膜和卤化物膜中电解质的分解温度;电解质层经粘结剂填充和压实,厚度小于硫化物膜和卤化物膜的厚度之和。本申请提供的技术方案,不仅可以降低制备流程的复杂度和制备成本,还可以降低界面阻抗,提高固态电池的界面本征稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018107A_ABST
    Figure CN123018107A_ABST
Patent Text Reader

Abstract

The application provides an electrolyte layer preparation method, an electrolyte, a battery cell and a solid-state battery, and relates to the technical field of solid-state batteries.The method comprises the following steps: laminating a sulfide film and a halide film to form a multi-film layer structure; and performing hot roller pressing on the multi-film layer structure to obtain an electrolyte layer; the temperature of the hot roller pressing is greater than the secondary glass transition temperature of a binder in the sulfide film and the halide film, and is less than the decomposition temperature of an electrolyte in the sulfide film and the halide film; and the electrolyte layer is filled and compacted by the binder, and the thickness is less than the sum of the thicknesses of the sulfide film and the halide film.The technical scheme provided by the application can not only reduce the complexity and preparation cost of the preparation process, but also reduce the interface impedance and improve the interface intrinsic stability of the solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solid-state battery technology, and in particular to a method for preparing an electrolyte layer, an electrolyte, a battery cell, and a solid-state battery. Background Technology

[0002] With the booming development of consumer electronics, new energy vehicles, and energy storage industries, lithium battery technology is advancing rapidly. The rise of high-end drones and intelligent robots has placed even more stringent demands on battery energy density, power density, safety, and cycle life. Compared to liquid batteries, solid-state batteries (SSBs), with their higher safety and energy density potential, have become a key path to overcome bottlenecks and the most powerful contender for next-generation high-performance energy storage systems. However, interfacial contact problems arise between the electrolyte layer and the positive and negative electrodes in solid-state batteries, reducing the intrinsic interfacial stability of the solid-state battery. Summary of the Invention

[0003] In view of this, embodiments of this application provide a method for preparing an electrolyte layer, an electrolyte, a battery cell, and a solid-state battery, for improving the intrinsic interfacial stability of solid-state batteries.

[0004] To achieve the above objectives, in a first aspect, embodiments of this application provide a method for preparing an electrolyte layer, the method comprising: Sulfide films and halide films are stacked to form a multi-layer film structure; The multi-layer structure is hot-rolled to obtain an electrolyte layer. The hot-rolling temperature is higher than the secondary glass transition temperature of the binder in the sulfide and halide films, but lower than the decomposition temperature of the electrolyte in the sulfide and halide films. The electrolyte layer is filled and compacted with binder, and its thickness is less than the sum of the thicknesses of the sulfide and halide films.

[0005] In one possible implementation of the first aspect, hot rolling of the multi-layer structure includes: The multi-layer film structure is subjected to a first hot roll pressing process and a second hot roll pressing process in sequence; the roll gap value of the first hot roll pressing process is greater than the roll gap value of the second hot roll pressing process.

[0006] In one possible implementation of the first aspect, after forming the multilayer structure and before hot rolling the multilayer structure, the method further includes: The multi-layer structure is preheated at a temperature lower than or close to the rolling temperature.

[0007] In one possible implementation of the first aspect, in the same hot rolling process, there is a temperature difference between the upper roll temperature and the lower roll temperature.

[0008] In one possible implementation of the first aspect, the method further includes: During the hot rolling process, the surface temperature of the multi-layer structure is detected; An alarm will be triggered if the surface temperature exceeds the decomposition temperature.

[0009] In one possible implementation of the first aspect, the sulfide film and the halide film are laminated, comprising: The sulfide film and halide film are cut to the same size and then stacked. Alternatively, the sulfide film and the halide are cut to the same size and then pulled to a hot roller press for lamination.

[0010] In one possible implementation of the first aspect, the sulfide membrane and the halide membrane are prepared using a dry process, wherein the halide membrane includes a halide electrolyte membrane and a halide oxide electrolyte membrane.

[0011] Secondly, embodiments of this application provide an electrolyte layer prepared using the method described in the first aspect or any embodiment of the first aspect.

[0012] Thirdly, embodiments of this application provide a battery cell comprising: a positive electrode, a negative electrode, and an electrolyte layer as described in the second aspect, wherein the positive electrode is in close contact with the halide film side of the electrolyte layer, and the negative electrode is in close contact with the sulfide film side of the electrolyte layer.

[0013] Fourthly, embodiments of this application provide a solid-state battery, which includes: a cell as described in the third aspect.

[0014] This application provides an electrolyte layer preparation method, an electrolyte, a battery cell, and a solid-state battery. The method includes: stacking a sulfide film and a halide film to form a multi-layer structure; hot-rolling the multi-layer structure to obtain an electrolyte layer; the hot-rolling temperature is higher than the secondary glass transition temperature of the binder in the sulfide and halide films, and lower than the decomposition temperature of the electrolyte in the sulfide and halide films; the electrolyte layer is filled and compacted with a binder, and its thickness is less than the sum of the thicknesses of the sulfide and halide films. The technical solution provided in this application not only reduces the complexity and cost of the preparation process but also reduces interfacial impedance and improves the intrinsic interfacial stability of the solid-state battery. Attached Figure Description

[0015] Figure 1 A schematic flowchart illustrating a method for preparing an electrolyte layer according to an embodiment of this application; Figure 2 This is a schematic diagram illustrating the preparation of the electrolyte layer provided in an embodiment of this application; Figure 3 A schematic flowchart illustrating another method for preparing an electrolyte layer provided in this application embodiment; Figure 4This is a schematic diagram of a temperature detection process provided in an embodiment of this application. Detailed Implementation

[0016] The embodiments of this application are described below with reference to the accompanying drawings. The terminology used in the implementation section of this application is only for explaining specific embodiments and is not intended to limit the application. The following specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described again in some embodiments.

[0017] With the continuous evolution of electrode technology, solid-state batteries are rapidly penetrating into diverse application scenarios. The core bottleneck in their development lies in the development of high-performance solid-state electrolytes (SSEs). While sulfides possess excellent ionic conductivity, they are limited by a narrow electrochemical window and air sensitivity, making them difficult to match with high-voltage cathodes and requiring complex synthesis. Halides, although exhibiting wide oxidation potentials and good cathode compatibility, suffer from thermodynamic instability with lithium metal on the anode side, leading to frequent interfacial side reactions and a sharp capacity decay.

[0018] In recent years, halide oxides have emerged as a new system. As a branch of halides, halide oxides combine the high oxidation stability and excellent kinetic properties (ionic conductivity >10) of halides. - ²S·cm - ¹, Operating temperature range as low as It has a temperature of 60℃ and better air stability; however, the reduction stability problem between it and the lithium metal anode has not been fundamentally solved, which is a key difficulty that needs to be overcome in the commercialization process of all-solid-state batteries.

[0019] Existing technologies primarily improve the interfacial contact between the electrolyte and the electrode through interfacial coating engineering (such as positive / negative electrode surface modification) and bulk doping control (adjusting electrolyte composition or elemental doping). While these methods can reduce interfacial impedance and alleviate interfacial instability to some extent, they often come with significant increases in manufacturing complexity and raw material costs. To address the limitations of interfacial compatibility in single-electrolyte systems, one improvement strategy is to construct a composite cathode heterostructure, introducing halides on the positive electrode side to withstand high voltages while integrating a sulfide interlayer on the negative electrode side to protect the lithium metal. However, this architecture inevitably induces a "three-phase boundary" effect at the interface between the composite cathode and the sulfide layer. Studies have shown that intrinsic electrochemical instability exists in this region, and chemical crosstalk caused by interfacial interdiffusion and phase transitions is the core mechanism leading to battery performance degradation, and this failure phenomenon is widespread.

[0020] To overcome the above limitations, a dual electrolyte layer structure (positive electrode – halide – sulfide – negative electrode) is provided, aiming to utilize the antioxidant properties of halides and the anti-reduction properties of sulfides, respectively. However, simple multilayer physical stacking not only reduces the overall energy density due to the introduction of excessive inactive components, but also generates significant interfacial transport impedance due to poor rigid contact between layers.

[0021] In view of this, the embodiments of this application provide an electrolyte layer that can avoid the three-phase boundary effect and does not rely on the cumbersome interface engineering of integrated electrolyte manufacturing technology. Moreover, the electrolyte layer can not only effectively improve the interfacial impedance of solid-solid contact (positive and negative electrodes and electrolyte layer), reduce interfacial side reactions, and build a stable and interconnected ion transport interface, thus achieving simultaneous improvement of the intrinsic stability and electrochemical performance of the interface of all-solid-state batteries, but also significantly reduce production costs through process simplification and is compatible with a variety of electrolyte systems. It has important research significance and practical value for the commercial application of solid-state batteries, thereby helping to break through the industrialization bottleneck of solid-state batteries.

[0022] Figure 1 This is a schematic flowchart of an electrolyte layer preparation method provided in an embodiment of this application, as shown below. Figure 1 As shown, the method may include the following steps: Step S110: Stack the sulfide film and the halide film to form a multi-layer structure.

[0023] Figure 2 This is a schematic diagram illustrating the fabrication of the electrolyte layer provided in an embodiment of this application. (See attached diagram.) Figure 2 The sulfide film and halide film can be separately drawn to a hot roller mill for stacking, so that the sulfide film and halide film are in close contact without obvious bubbles or wrinkles. In the embodiments of this application, the halide film may include a halide electrolyte film and a halide oxide electrolyte film.

[0024] In some embodiments, sulfide films and halide films can be cut to the same size and stacked inside a glove box.

[0025] When the multilayer structure includes two layers, the stacking order of the sulfide film and the halide film is not limited; when the multilayer structure includes three or more layers, taking two halide films and one sulfide film as an example, the same halide film layers are adjacent.

[0026] In some embodiments, during the continuous production of sulfide and halide films, the sulfide and halide films can be cut to the same size and then drawn separately to a hot roller press for subsequent electrolyte layer preparation processes. The cutting size of the sulfide and halide films can be selected according to actual needs, and this application embodiment does not impose any particular limitation on this.

[0027] In some embodiments, the sulfide film and the halide film can be cut to the same size and then stacked in the glove box to ensure that the edges of the sulfide film and the halide film are aligned, avoiding the covering effect and poor edge interface bonding caused by size differences, thereby ensuring the uniformity of interface bonding after rolling.

[0028] Sulfide and halide membranes can be prepared using dry processes to reduce preparation costs while ensuring the ionic conductivity of the membrane.

[0029] Taking the preparation of halide membranes as an example, halide electrolytes and binders can be stirred and mixed to obtain a homogeneous mixture. Then, shear force is applied to the mixture to complete the fiberization. After that, the fiberized mixture can be rolled to obtain a halide membrane.

[0030] The preparation process for sulfide films is similar. An exemplary binder is polytetrafluoroethylene (PTFE). Of course, other polymers can also be used as binders, which will not be elaborated further in this application.

[0031] The following example illustrates the preparation of sulfide and halide membranes using a dry method.

[0032] The halide electrolyte can be Li3InCl6, Li3ZrCl6, or Li3YBr. x Cl 6-x (The ratio of Br to Cl is adjustable, x∈[0,6]), Li 1.75 ZrCl 4.75 O 0.5 LiTaOCl4 or other electrolytes suitable for all-solid-state batteries. Sulfide electrolytes can be Li 5.5 PS 4.5 Cl 1.5 LiPSClBr2, Li 10 GeP2S 12 Or other electrolytes suitable for all-solid-state batteries.

[0033] In some embodiments, the areal density ratio of the sulfide film to the halide film can be 1:9 to 9:1, and the preferred ratio can be 5:8 to 8:5.

[0034] Step S120: Hot roll pressing is performed on the multi-layer structure to obtain the electrolyte layer.

[0035] Hot rolling can be a single-pass process, meaning that after the multi-layer film structure is centered and fed in, the electrolyte layer is obtained after rolling. The temperature of a single-pass hot rolling process can be higher than the secondary glass transition temperature (T0) of the binder in sulfide and halide films. g2And it is lower than the decomposition temperature of the electrolyte in sulfide and halide films. Among them, the secondary glass transition temperature T... g2 This refers to the characteristic temperature at which the amorphous region of the binder can be activated to generate greater chain segment movement. This is achieved by controlling the temperature of the hot rolling process to be higher than the secondary glass transition temperature T. g2 This process allows the binder to enter a highly elastic state and soften, significantly enhancing the mobility of its molecular chain segments. The material exhibits excellent flexibility and deformability while maintaining high bulk strength and molecular weight integrity. Based on this, during subsequent cooling, the binder can tightly encapsulate the electrolyte particles and form a continuous network structure. Furthermore, the electrolyte layer, filled and compacted by the binder, has a thickness less than the sum of the thicknesses of the sulfide and halide films.

[0036] It should be noted that if the sulfide film and the halide film use the same binder, the secondary glass transition temperature T of the sulfide film and the halide film will be... g2 Similarly, the roller temperature of hot rolling (hereinafter referred to as roller temperature) is greater than the secondary glass transition temperature T of the binder. g2 Furthermore, the temperature should be lower than the decomposition temperature of the electrolyte in the sulfide and halide films; if different binders are used for the sulfide and halide films, the roller temperature can be higher than the secondary glass transition temperature T of the respective binders in the sulfide and halide films. g2 The maximum value in the range is less than the decomposition temperature of the electrolyte in sulfide and halide films.

[0037] By making the roller temperature higher than the secondary glass transition temperature T g2 Furthermore, the roller temperature is lower than the decomposition temperature of the electrolyte. This allows for greater segmental movement in the amorphous regions of the binder, completing the entire process of "high-temperature softening and deformation - filling and encapsulation - cooling and shaping - mechanical interlocking and curing." This ensures the binder fully fills the gaps between solid electrolyte particles, facilitating the formation of a stable mechanical interlocking structure after cooling and shaping. This significantly improves the density and interfacial bonding of the electrolyte sheet, achieving tight encapsulation between particles through the full movement of chain segments, resulting in a solid electrolyte electrode sheet with excellent mechanical properties and ion conductivity. Simultaneously, the roller temperature is lower than the decomposition temperature of the electrolyte, completely avoiding high-temperature-induced electrolyte material decomposition and interfacial side reactions. This ensures the ionic conductivity and electrochemical stability of the solid electrolyte, resulting in a higher density composite electrolyte layer, a more continuous ion conduction path, and a significant improvement in overall ionic conductivity.

[0038] In some embodiments, the temperature of the hot rolling press can be controlled to be greater than the secondary glass transition temperature T of the binder in the sulfide film and halide film. g2 Furthermore, the temperature is lower than the decomposition temperature of the adhesive and the electrolyte, thereby improving the stability and ionic conductivity of the electrolyte layer.

[0039] In some embodiments, the centering feed can be achieved by using a guide clamp to ensure that the multi-layer structure can be fed in along the center line of the roll gap, thus avoiding interlayer slippage and misalignment that could lead to uneven film thickness or edge wrinkles.

[0040] Optionally, see Figure 2 The hot rolling process can be a multi-pass hot rolling process. For example, after centering and feeding, the multi-layer film structure can be rolled sequentially through a first hot rolling process and a second hot rolling process. The first and second hot rolling processes can each include multiple passes; for example, both the first and second hot rolling processes can include 1 to 5 passes.

[0041] In one alternative implementation, the roll gap value of the first hot rolling process can be greater than that of the second hot rolling process. For example, the roll gap of the first hot rolling process can be slightly smaller than the sum of the thicknesses of the sulfide film and the halide film (e.g., a compression ratio of 10%) to degas the multilayer film structure.

[0042] Optionally, the output status of the process can be monitored in real time during the first hot rolling process. When wavy wrinkles appear at the edges of the multi-layer structure, the wavy wrinkles can be reduced by adjusting the parallelism of the rollers.

[0043] In one embodiment, the interfacial bonding state between the sulfide film and the halide film can be evaluated in real time by online impedance monitoring or optical detection to avoid excessive rolling pressure leading to pore closure and ion transport obstruction, or insufficient rolling pressure leading to poor solid-solid contact and excessively high interfacial impedance. The rolling pressure range of the first hot rolling process can be exemplarily 3~10 MPa.

[0044] Online impedance monitoring can include, for example, AC impedance spectroscopy, four-probe method and thin film contact resistance test, etc. Optical detection can include, for example, charge-coupled device (CCD) camera visual inspection, laser triangulation and optical coherence tomography (OCT), etc. The specific method used can be selected according to actual needs, and the embodiments of this application do not impose any special limitations.

[0045] After the first hot rolling process, a second hot rolling process can be used to roll the multi-layer structure. The roll gap value of the second hot rolling process can be smaller than that of the first hot rolling process, so that the compression ratio can be increased to 20%~30%. The rolling pressure range of the second hot rolling process can be 5~20 MPa for example.

[0046] In some embodiments, the roller gap value of the second hot rolling process can be gradually reduced. By gradually reducing the roller gap value of the second hot rolling process, the problems of local fragmentation and edge overflow caused by direct rolling with a large compression ratio in a single operation can be avoided. By applying pressure gradually, the sulfide and halide electrolyte particles can gradually complete uniform plastic deformation, and finally the overall compression ratio can be stably increased to 20%~30%. This can not only further improve the density of the composite electrolyte layer and eliminate the internal residual micropores, but also ensure the uniformity of the film thickness, avoid ion channel blockage caused by local overpressure, and significantly improve the overall ionic conductivity and mechanical stability of the composite electrolyte.

[0047] Optionally, the roll temperature of the first hot rolling process can be lower than that of the second hot rolling process, so as to heat the multi-layer structure through the first hot rolling process.

[0048] Optionally, the roll temperature of the first hot rolling process can be the same as that of the second hot rolling process.

[0049] For ease of explanation, the following example illustrates the situation where the roll temperature of the first hot rolling process is the same as that of the second hot rolling process.

[0050] For example, in the same hot rolling process, there can be a temperature difference between the upper and lower rolls, which can be 5~10℃, to promote heat conduction. For example, the upper roll temperature range can be 60~120℃, and the lower roll temperature range can be 55~115℃.

[0051] If the sulfide film and halide film are prepared using a binder-free process, the hot rolling temperature can be referenced to the softening temperature of the residual polymer in the film or the intrinsic β-transition temperature of the electrolyte. The hot rolling temperature can be exemplarily 60~120℃.

[0052] Optionally, the roller speed of the hot rolling process can be 0.5~5m / min to avoid microcracks or internal stress accumulation in the film material due to instantaneous large deformation, thereby improving the reliability and yield of the preparation process.

[0053] It is understood that the rolling temperature shown in this embodiment is exemplary, and its specific value can be selected according to actual needs.

[0054] See Figure 3 After step S110 and before step S120, the method may further include step S130.

[0055] Step S130: Preheat the multi-layer structure.

[0056] Before the multi-layered structure enters the roll gap, it is preheated to soften it and prevent the cold film from contacting the hot roll, which could cause a sudden temperature drop and localized cracking. The preheating time can be selected according to actual needs, for example, 1-2 minutes.

[0057] Optionally, the preheating temperature can be less than or close to the roll forming temperature. For example, the difference between the roll temperature and the preheating temperature can be greater than 0 and less than the target temperature threshold. The specific preheating temperature can be selected according to actual needs.

[0058] In the hot rolling process, the thermal energy of the roll temperature can activate a larger range of chain segment movement in the amorphous region of the binder in the sulfide film and halide film. At the same time, under the gradient pressure and thermo-mechanical coupling effect of the first and second hot rolling processes, the softened binder fills the micro-gaps between the layers, promoting the formation of a tight bond at the contact interface between the sulfide film and the halide film, that is, the fusion of the heteroelectrolyte interface occurs, thereby obtaining a uniform and stable electrolyte layer.

[0059] In some embodiments, see Figure 4 In the hot rolling process, the method may further include steps S210 and S220.

[0060] Step S210: Detect the surface temperature of the multi-layer structure.

[0061] Optionally, an infrared thermal imager can be used to monitor the temperature changes of the material surface in the rolling area in real time to ensure that the actual temperature of the multi-film structure is always lower than the decomposition temperature of the electrolyte.

[0062] Step S220: If the surface temperature is greater than the decomposition temperature of the electrolyte in the sulfide film and halide film, an alarm will be triggered.

[0063] In some embodiments, when the surface temperature is detected to be higher than the decomposition temperature of the electrolyte, an alarm can be issued to the staff through sound alarm, flashing light alarm, interface pop-up prompt or SMS reminder, so that they can adjust the roller temperature in time to ensure that the actual temperature of the multi-film structure is always lower than the decomposition temperature of the electrolyte.

[0064] Considering that the electrolyte layer is at a high temperature and under pressure immediately after exiting the roller, the electrolyte layer can optionally be allowed to cool naturally or under pressure to room temperature in order to fully release internal stress.

[0065] Optionally, during cooling, the cooling rate can be controlled (e.g., 5-10℃ / min) to avoid uneven distribution of internal thermal stress due to sudden temperature drops, which could lead to structural defects such as film cracking, interlayer delamination, or micropores. After the electrolyte layer cools to room temperature, uneven or rough edges can be trimmed to obtain an integrated multilayer composite electrolyte membrane (i.e., electrolyte layer) with no air gaps at the interface and high bonding strength.

[0066] In this embodiment, the hot rolling process activates greater chain segment movement in the amorphous regions of the binder in the sulfide and halide films, allowing them to permeate into the film voids with thermal assistance, resulting in a tight fusion of the two films. This not only eliminates physical gaps between layers but also significantly increases the effective contact area between particles. This not only solves the interfacial resistance problem inherent in traditional physical stacking but also combines the advantages of high ionic conductivity of sulfides with high compatibility of halides, enabling rapid and uniform lithium-ion transport within the multilayer film, thereby improving the battery's rate performance and low-temperature performance.

[0067] Furthermore, the dense, integrated multilayer composite electrolyte membrane formed by hot rolling combines the toughness of sulfides with the rigidity of halides, effectively buffering volumetric stress during charging and discharging to prevent brittleness and peeling. Simultaneously, this process is a continuous, low-energy thin-film preparation technology, requiring no high-temperature sintering or prolonged pressure holding. It is compatible with various electrolyte systems and easily integrates with existing roll-to-roll production lines, reducing assembly misalignment risks and significantly lowering the manufacturing cost and mass production difficulty of all-solid-state batteries, demonstrating excellent practicality and applicability.

[0068] Those skilled in the art will understand that the above embodiments are exemplary and not intended to limit this application. Where possible, the execution order of one or more of the above steps can be adjusted, or they can be selectively combined to obtain one or more other embodiments. Those skilled in the art can arbitrarily select and combine the above steps as needed, and all those that do not depart from the essence of this application fall within the protection scope of this application.

[0069] Based on the same inventive concept, this application provides an electrolyte layer that can be prepared using the above-described method.

[0070] The electrolyte layer prepared in this application embodiment can be applied to fields such as high-energy-density power solid-state batteries, wide-temperature-range energy storage systems, and high-performance consumer electronics power supplies.

[0071] This application also provides a solid-state battery, which may include a cell, and the cell may include a positive electrode, a negative electrode and an electrolyte layer prepared in the above method embodiments, wherein the positive electrode may be in close contact with the halide film side of the electrolyte layer and the negative electrode may be in close contact with the sulfide film side of the electrolyte layer.

[0072] For example, in specific applications, this electrolyte layer can be directly used to replace the traditional single electrolyte layer. During cell assembly, its "soft and hard bonding" characteristics can be utilized to tightly attach high-voltage positive electrodes such as high-nickel ternary or lithium-rich manganese-based electrodes to the high-voltage-resistant halide side, and lithium metal or silicon-carbon negative electrodes to the interface-stable sulfide side, thereby constructing an asymmetric structure of "positive electrode-halide / sulfide-negative electrode", which is then integrated and laminated.

[0073] The positive electrode can be one or more of layered oxide positive electrode materials, spinel type positive electrode materials, or polyanionic positive electrode materials, preferably high-nickel ternary positive electrode material LiNi. x Co y Mn z O2, where 0.5≤x≤0.9, 0.05≤y≤0.3, 0.05≤z≤0.3; it can also be LiCoO2, LiMn2O4, LiFePO4, etc. The preferred median particle size is D. 50 The size is 1~20μm. The conductive agent can be Super P Li, acetylene black, vapor-grown carbon fiber (VGCF), carbon nanotube (CNT) or a combination thereof.

[0074] The electrolyte in the composite cathode can be the same as or different from the electrolyte on the contact side of the electrolyte layer, depending on actual needs. This application does not impose any particular limitation on this. The mass ratio of the cathode, electrolyte, and conductive agent in the composite cathode can be 50-95 wt%, 3-45 wt%, and 1-10 wt%, respectively.

[0075] The negative electrode can be made of lithium-indium alloy, metallic lithium, graphite-based negative electrode, silicon-carbon negative electrode, etc. Lithium-indium alloy is preferred as the counter electrode or reference negative electrode for performance verification. In the composite negative electrode, the electrolyte is the electrolyte corresponding to the contact side of the electrolyte layer. The mass ratios of the negative electrode, electrolyte, and conductive agent are 50–95 wt%, 3–45 wt%, and 0–10 wt%, respectively. It should be understood that the specific types of the positive electrode, conductive agent, and negative electrode can also be selected according to actual needs.

[0076] All-solid-state batteries are assembled using molding or stacking methods, and their first-cycle charge / discharge capacity, rate performance, cycle life, and interface impedance are tested. Interface impedance can be obtained through AC impedance testing, with a test frequency range of 1MHz to 0.1Hz and a perturbation voltage of 5 to 10mV.

[0077] By employing a hot roll forming process to tightly bond sulfide and halide films and directionally assemble them, the electrochemical stability window can be effectively broadened. This process suppresses high-voltage oxidative decomposition on the positive electrode side while ensuring stability of lithium metal on the negative electrode side. It also improves the solid-solid contact between the electrode and electrolyte in solid-state batteries, effectively avoids complex interface problems, reduces interface side reactions, and constructs a stable and interconnected ion transport interface, thereby reducing interface impedance and achieving a simultaneous improvement in the intrinsic stability of the interface and the electrochemical performance of all-solid-state batteries.

[0078] Furthermore, by adopting the above-described implementation method, the solid-solid interface impedance can be significantly reduced and the volumetric strain during charge and discharge can be buffered, thereby improving the energy density, cycle life, and rate performance of all-solid-state lithium batteries. Moreover, it achieves dense cell packaging without the need for additional interface modification layers, making it particularly suitable for large-scale roll-to-roll continuous production processes. While improving battery safety, it effectively solves the problems of interface oxidation decomposition and lithium dendrite puncture under high voltage, meeting the stringent requirements of electric vehicles and high-end energy storage devices for long cycle life and high power output.

[0079] The following examples illustrate the performance test results of the electrolyte layer and / or solid-state battery of this solution.

[0080] Example 1: First, sulfide and halide films of appropriate thicknesses were prepared by roll forming, and then drawn onto a hot roll mill for stacking. During stacking, it was ensured that the two films were in close contact without obvious bubbles or wrinkles. The areal density ratio of the LiPSClBr2 (LPSCB) film to the Li3InCl6 (LIC) film was approximately 5:8, with thicknesses of 90 μm and 100 μm, respectively.

[0081] Next, the hot roller press was turned on, and the upper and lower rollers were heated to 95℃ and 90℃ respectively. The stacked LSPCB-LIC film was preheated for 2 minutes in front of the roller gap, and then fed perpendicularly to the roller surface. The roller pressing linear speed was set to 1m / min. During the roller pressing degassing and shaping process, the roller pressing was carried out gradually with pressures of 8MPa and 15MPa respectively, and the roller gap was gradually reduced to toughen and thin the electrolyte layer.

[0082] Then, the electrolyte layer that just exited the roller was cooled to room temperature, and then the uneven parts at the edges were trimmed to obtain an integrated LSPCB / LIC composite electrolyte membrane (i.e., LSPCB / LIC electrolyte layer) with high bonding strength.

[0083] Finally, the resulting composite negative electrode (artificial graphite:LSPCB=6:4, PTFE content 2%), LSPCB / LIC composite electrolyte membrane, and composite positive electrode (LiNi) were combined. 0.8 Co 0.1 Mn 0.8 O2 (abbreviated as NCM811): LIC: Super P Li=6:3:1, PTFE content 2%) is assembled into a molded solid-state battery according to the structure of the positive electrode corresponding to the composite electrolyte membrane LIC side and the negative electrode corresponding to the LSPCB side.

[0084] Electrochemical performance tests were conducted on the solid-state battery at 25°C and within a voltage window of 2.75V to 4.1V. The results showed that, compared to the comparative example, the solid-state battery assembled in this embodiment exhibited lower interfacial impedance and superior cycle stability. Specifically, this solid-state battery demonstrated higher first-cycle charge specific capacity, first-cycle discharge specific capacity, and corresponding first-efficiency (the ratio of first-cycle discharge specific capacity to first-cycle charge specific capacity) at 0.1C, and its capacity retention was significantly improved compared to the comparative sample after 100 cycles at 0.2C.

[0085] Example 2: Due to the adjustment of the electrolyte membrane type, the upper and lower rollers were set to 80℃ and 75℃ respectively. Simultaneously, during the roller pressing venting and setting processes, the roller pressure was adjusted to 5 MPa and 10 MPa, with other conditions remaining the same as in Example 1. After cooling, a high-bonding-strength integrated Li₂ was obtained. 1.75 ZrCl 4.75 O 0.5 / Li 5.5 PS 4.5 Cl 1.5 Composite electrolyte membrane (i.e., LZCO / LPSC electrolyte layer).

[0086] Electrochemical tests were conducted on solid-state batteries assembled according to the corresponding structure. The results showed that the solid-state battery assembled with LZCO / LPSC composite electrolyte membrane significantly improved the first charge specific capacity, first discharge specific capacity, and first efficiency compared to Example 1, and had better rate performance. Although its cycle performance was slightly worse than that of Example 1, it was significantly better than that of the comparative example.

[0087] Example 3: Compared to Example 2, the electrolyte in the composite cathode was changed to LIC, combined with an LZCO / LPSC electrolyte layer, and a solid-state battery with inconsistent electrolytes on the contact side of the composite cathode and electrolyte layer was assembled and tested.

[0088] The results show that, compared with Example 1, this solid-state battery exhibits higher first-charge specific capacity, first-discharge specific capacity, and higher rate performance, and its first efficiency is also higher than that of Example 1. Its cycle performance is between that of Example 1 and Example 2.

[0089] Example 4: Except for the areal density ratio of sulfide film to halide, the preparation conditions were the same as in Example 1. The areal density ratios were set to 1:4, 5:8, 8:5, and 2:1.

[0090] The results show that when the areal density ratio of the two components is controlled at around 5:8 to 8:5, the overall performance of the electrolyte layer is optimal. This ensures both the excellent bulk ion conductivity of the sulfide and improves the battery's cycle stability by utilizing the interfacial stabilizing effect of the halide. Furthermore, excessively high or low areal density ratios can lead to an imbalance in battery performance.

[0091] Comparative Example 1: An all-solid-state battery was assembled according to the "positive electrode-halide-sulfide-negative electrode" structure. Its electrolyte layer was prepared by simple physical stacking. The results showed that its first-cycle capacity was lower than that of Comparative Example 2, and its capacity retention rate was better than that of Comparative Example 2. However, its cycle stability and rate performance were lower than those of Examples 1 and 2.

[0092] Comparative Example 2: A solid-state battery was assembled directly using a "positive electrode-sulfide-negative electrode" structure. The results showed that its initial capacity was acceptable, but the interfacial impedance increased rapidly during cycling, and its rate performance and cycle life were significantly lower than those of Examples 1 and 2.

[0093] Table 1 shows partial data of the all-solid-state mold batteries of Examples 1-3 and Comparative Examples 1 and 2 provided in the embodiments of this application.

[0094]

[0095] The naming or numbering of steps in this application does not mean that the steps in the method flow must be executed in the time / logical order indicated by the naming or numbering. The execution order of the named or numbered process steps can be changed according to the technical purpose to be achieved, as long as the same or similar technical effect can be achieved.

[0096] In the above embodiments, the descriptions of each embodiment have different focuses. For parts that are not described in detail or recorded in a certain embodiment, please refer to the relevant descriptions of other embodiments.

[0097] In the embodiments provided in this application, it should be understood that the disclosed apparatus / devices and methods can be implemented in other ways. For example, the apparatus / device embodiments described above are merely illustrative. For instance, the division of modules or units is only a logical functional division, and in actual implementation, there may be other division methods. For example, multiple units or components may be combined or integrated into another system, or some features may be ignored or not executed. Furthermore, the coupling or direct coupling or communication connection shown or discussed may be through some interfaces; the indirect coupling or communication connection between apparatuses or units may be electrical, mechanical, or other forms.

[0098] It should be understood that, when used in this application specification and the appended claims, the term "comprising" indicates the presence of the described features, integrals, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, integrals, steps, operations, elements, components and / or a collection thereof.

[0099] In the description of this application, unless otherwise stated, " / " indicates that the objects before and after are in an "or" relationship. For example, A / B can mean A or B. "And / or" in this application is merely a description of the relationship between the related objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist simultaneously, and B exists alone. A and B can be singular or plural.

[0100] As used in this application specification and the appended claims, the term "if" may be interpreted, depending on the context, as "when," "once," "in response to determination," or "in response to detection." Similarly, the phrase "if determined" or "if detected [the described condition or event]" may be interpreted, depending on the context, as meaning "once determined," "in response to determination," "once detected [the described condition or event]," or "in response to detection [the described condition or event]."

[0101] Furthermore, in the description of this application and the appended claims, the terms "first," "second," "third," etc., are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments described herein can be implemented in a sequence other than that illustrated or described herein.

[0102] References to "one embodiment" or "some embodiments" in this specification mean that one or more embodiments of this application include a specific feature, structure, or characteristic described in connection with that embodiment. Therefore, the phrases "in one embodiment," "in some embodiments," "in other embodiments," "in still other embodiments," etc., appearing in different parts of this specification do not necessarily refer to the same embodiment, but rather mean "one or more, but not all, embodiments," unless otherwise specifically emphasized.

[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A method for preparing an electrolyte layer, characterized in that, include: Sulfide films and halide films are stacked to form a multi-layer film structure; The multi-film structure is hot-rolled to obtain an electrolyte layer; The temperature of the hot roller pressing is greater than the secondary glass transition temperature of the binder in the sulfide film and the halide film, and less than the decomposition temperature of the electrolyte in the sulfide film and the halide film; the electrolyte layer is filled and compacted by the binder, and its thickness is less than the sum of the thicknesses of the sulfide film and the halide film.

2. The method according to claim 1, characterized in that, The hot rolling of the multi-layer structure includes: The multi-film structure is subjected to a first hot rolling process and a second hot rolling process in sequence; the roller gap value of the first hot rolling process is greater than the roller gap value of the second hot rolling process.

3. The method according to claim 1, characterized in that, After the formation of the multi-film structure and before the hot rolling of the multi-film structure, the method further includes: The multi-layer structure is preheated at a temperature less than or close to the rolling temperature.

4. The method according to claim 1, characterized in that, In the same hot roll forming process, there is a temperature difference between the upper roll temperature and the lower roll temperature.

5. The method according to claim 1, characterized in that, The method further includes: During the hot rolling process, the surface temperature of the multi-film structure is detected; An alarm is triggered if the surface temperature exceeds the decomposition temperature.

6. The method according to claim 1, characterized in that, The process of stacking sulfide films and halide films includes: The sulfide film and the halide film are cut to the same size and then stacked. Alternatively, the sulfide film and the halide film can be cut to the same size and then pulled to a hot roller press for lamination.

7. The method according to any one of claims 1-6, characterized in that, The sulfide membrane and halide membrane are prepared using a dry process. The halide membrane includes a halide electrolyte membrane and a halide oxide electrolyte membrane.

8. An electrolyte layer, characterized in that, The electrolyte layer is prepared using the method described in any one of claims 1-7.

9. A battery cell, characterized in that, include: The electrode comprises a positive electrode, a negative electrode, and an electrolyte layer as described in claim 8, wherein the positive electrode is in close contact with the halide film side of the electrolyte layer, and the negative electrode is in close contact with the sulfide film side of the electrolyte layer.

10. A solid-state battery, characterized in that, include: The battery cell as described in claim 9.